Qualidade de vida de pacientes coinfectados por hanseníase e HIV/AIDS em tratamento ambulatorial no Núcleo de Medicina Tropical da Universidade Federal do Pará - SILVA, Maria Josiane Brito (2019)
Leprosy represents a serious public health problem in Brazil, being marked by the psychological repercussion and physical disabilities resulting from the disease process. Such disease, as well as HIV/AIDS, can cause physical and emotional disorders, which can be an aggravating factor in the quality of life of HIV/AIDS coinfected leprosy patients. A comparative cross-sectional study was conducted with 53 patients using the Short Medical Outcomes Study 36 – Item Short-form Health Survey (SF- 36) and the supplementary questionnaire to assess the quality of life of leprosy and coinfected patients in the Ambulatory of the Nucleus of Tropical Medicine of the Federal University of Pará. This study demonstrated that through the eight domains (functional capacity, physical aspects, emotional aspects, pain, general health status, vitality, social aspects and mental health) of the quality of life questionnaires, coinfected patients presented a worse quality of life, because they exhibited lower scores than non-coinfected patients.